Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi SAK ETAP, Dan Pelatihan Penyusunan Laporan Keuangan Terhadap Kualitas Laporan Keuangan BUMDes : Studi Kasus BUMDes Se-Kecamatan Bendosari - Amin, Reggy Aditya; Ningsih, Suhesti; Pravasanti, Yuwita Ariessa (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the influence of education level, understanding of SAK ETAP accounting standards, and training in financial report preparation on the quality of Village-Owned Enterprises (BUMDes) financial reports in Bendosari District. The research employs a quantitative approach with a population consisting of all staff and members of BUMDes. A purposive sampling technique was applied, resulting in 80 respondents from 10 BUMDes. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 23. Hypotheses were tested using the t-test, F-test, and the coefficient of determination (R²). The findings reveal that education level, understanding of SAK ETAP accounting, and financial reporting training have a positive and significant effect on the quality of BUMDes financial reports. This study highlights the importance of strengthening human resource competencies in BUMDes through education, adherence to accounting standards, and continuous training programs to enhance accountability and financial transparency at the village level.